2010
DOI: 10.1111/j.1744-7348.2010.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual reproduction and soil tillage effects on virulence of Pyrenophora teres in Finland

Abstract: Knowledge of the virulence of a pathogen population and recognition of the risks of changes in the virulence spectrum are essential in breeding crops for disease resistance. Sexual recombination in a pathogen increases the level of genotypic diversity and can influence the virulence spectrum. This study aimed to determine how sexual recombination can change virulence of the barley pathogen Pyrenophora teres and whether the barley cultivation system, no-tillage or normal tillage, influences P. teres virulence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…New epidemics of the net blotch recently have been reported around the world (McLean et al, 2009; Liu and Friesen, 2010). Development of resistant varieties is the most cost‐efficient method for control of net blotch (Jalli, 2010a, b). Silvar et al (2010) reported finding few examples of resistance to net blotch in the Spanish barley core collection.…”
Section: Focused Identification Of Germplasm Strategymentioning
confidence: 99%
“…New epidemics of the net blotch recently have been reported around the world (McLean et al, 2009; Liu and Friesen, 2010). Development of resistant varieties is the most cost‐efficient method for control of net blotch (Jalli, 2010a, b). Silvar et al (2010) reported finding few examples of resistance to net blotch in the Spanish barley core collection.…”
Section: Focused Identification Of Germplasm Strategymentioning
confidence: 99%
“…PTM appears to have spread since, being noted in Australia in 1977 ( Khan and Tekauz, 1982 ) and in Montana, United States in 1981 ( Bockelman et al, 1983 ). Although artificial hybrids can be readily made in the laboratory ( McDonald, 1967 ; Smedegård-Petersen, 1977a ; Campbell and Crous, 2003 ; Jalli, 2011 ), PTT and PTM are considered to be genetically autonomous populations ( Rau et al, 2003 , 2007 ; Bakonyi and Justesen, 2007 ; Bogacki et al, 2010 ; Lehmensiek et al, 2010 ; Leišová-Svobodová et al, 2014 ; Akhavan et al, 2016 ). Natural hybrids appear to be rare and have been suggested by RAPD and AFLP studies ( Campbell et al, 2002 ; Leišova et al, 2005 ; McLean et al, 2014 ), and recently confirmed by Poudel et al (2017) using form-specific markers.…”
Section: Introductionmentioning
confidence: 99%
“…However, a lack of field hybrids suggests a natural barrier to fertility as found by Smedegård-Petersen (1977a) or a fitness penalty. The significance of such field hybrids is they may potentially increase population genetic diversity, resistance to fungicides and form new virulence combinations ( Campbell et al, 1999 ; Jalli, 2011 ) although their contribution in these respects is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Fungicide usage in Finland re mains low compared to other European countries (Heinonen et al 2013). However, a significant im provement in the level of net blotch resistance has been found in the European barley cultivars released during the last 40 yr (Jalli 2011). Net blotch is the most common plant disease found in barley in Finland.…”
Section: Agro-management Effects On Yield Trendsmentioning
confidence: 99%